The Beth Ha-shitta Mosaic Floor –A New Perspective on the Light of Samaritan Oil Lamps - Sussman, V. (Liber Annuus, 2004)
Abstract The article analyzes the motifs on the mosaic pavement of Beth Hashitta, in comparison with motifs on Samaritan lamps, and shows a close connection between the mosaic and the lamps. A common ideological background and common regional roots can be identified between the mosaic and the Samaritan lamps. The article endeavours to indicate meanings to some of the motifs that appear on the pavement and on the lamps.